Effect of Shade Levels on Growth and Vigour of Seedlings of Terminalia Species in the Nursery - Prasad G (Department of Tree Physiology and Breeding, College of Forestry, 2002)
The present study was undertaken at the College of Forestry, Kerala Agricultural University, Vellanikkara, Thrissur during the period from 2000 to 2002 to evaluate the effect of various shade levels on the growth and vigour of seedlings of tembavu [Terminalia tomentosa var. crenulata (Roth.) C1.], thanni [t bellirica (Gaertn.) Roxb.] and neermaruthu [T. arjuna (Roxb. ex DC.) Wt. & Am.] in the nursery. The study revealed that in general, in all the species examined, shade exerted significant influence on growth and vigour of the seedlings in the nursery. In T. tomentosa and T. bellirica, 50 per cent shade produced best results with regard to shoot growth parameters like height and collar girth while in T. arjuna, 75 per cent shade was found to be most ideal with regard to these growth parameters. In general, in all the species, seedlings grown under 75 per cent shade produced maximum leaf number and area. The root growth parameters viz., length and spread . were found to be the maximum when grown under 50 per cent shade in T. tomntosa and T. bellirica, while 75 per cent was found to be the best for T. arjuna. Similarly, 50 per cent shade was found to be better for T. bellirica and T. tomentosa withregard to biomass production. However, T. arjuna responded well to 75 per cent shade in this regard. No clear cut trend was seen in the chlorophyll production with regard to the different shade levels in any of the three species studied. However, chlorophyll a, chlorophyll b and total chlorophyll content was slightly higher when grown under 75 per cent shade conditions. The highest number of stomata was seen when the plants